Improved transcriptome assembly and functional annotation of Pleurodeles waltl for regeneration research. - Mhd Yousuf Yassouf; Akira Kinoshita; Md Mahmudul Hasan; Tao-Sheng Li (PLoS ONE)
In this study, we present an updated transcriptome assembly for the Iberian ribbed newt, Pleurodeles waltl (P. waltl), a widely used model organism in regeneration research. The existing publicly available transcriptome for this species is limited by the inclusion of only three libraries from the limb and two from the heart, tissues of particular interest for regeneration studies. Additionally, the previous annotation was limited, reducing the utility of the dataset for further in-depth research. To provide a more complete transcriptome with a more comprehensive annotation, we utilized 58 previously published and 9 newly sequenced libraries, expanding the available transcriptomic data for key tissues, especially limb and heart tissues. Our assessment demonstrates that the new assembly offers a more comprehensive representation of reads and proteins compared to previous versions. Furthermore, we significantly improved the functional annotation by using the Trinotate pipeline, which includes the identification of complete ORFs, Pfam motifs, gene names, GO terms, and KEGG Orthology, facilitating more robust transcriptomic analyses. We also examined various stages of limb regeneration and development, gaining insights into the key signaling pathways involved. This work provides a valuable resource for researchers investigating the molecular mechanisms underlying P. waltl's regenerative abilities, enabling more detailed gene expression studies and broader biological insights.